2020
DOI: 10.1155/2020/1630890
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Glucosamine Supplementation in Premating Drinking Water Improves Within‐Litter Birth Weight Uniformity of Rats Partly through Modulating Hormone Metabolism and Genes Involved in Implantation

Abstract: Within-litter birth weight variation in multiparous animals has become a big issue due to high incidence of low birth weight neonates, which gives rise to high preweaning mortality and morbidity. Foetus with various birth weights is the outcome of diverse embryos competence which is affected by oocyte quality. Glucosamine (GlcN) has been reported to be involved in oocyte maturation; however, its effect on pregnant outcomes remains unknown. The present study was conducted to investigate the effects of premating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Notwithstanding, there exist certain biological indications that lend credence to the probability of the amplified risk that we have witnessed in instances of prostate cancer. Li Feng et al reported habitual glucosamine consumption has the potential to trigger an increase in the levels of insulin-like growth factor-I, known to be a contributing factor to the risk of prostate cancer ( Travis et al, 2016 ; Feng et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, there exist certain biological indications that lend credence to the probability of the amplified risk that we have witnessed in instances of prostate cancer. Li Feng et al reported habitual glucosamine consumption has the potential to trigger an increase in the levels of insulin-like growth factor-I, known to be a contributing factor to the risk of prostate cancer ( Travis et al, 2016 ; Feng et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…(33) However, some biological evidence has also been available to support the possibility of the increased risk we observed in prostate cancer. A recent experimental study reported that glucosamine supplementation could increase the concentration of insulin-like growth factor (IGF-I), (34) which is considered as a risk factor for prostate cancer. (35,36) No previous studies have reported related evidence in terms of glucosamine supplements and increased risk of skin cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%